Pengaruh Belanja Pemerintah Untuk Pendidikan Dan Kesehatan Terhadap Kualitas Sumberdaya Manusia (Human Capital) Kabupaten/Kota Di Kalimantan Selatan Dan Kalimantan Timur - Normaida Normaida; Yana Ulfah; Rian Hilmawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to analyze the influence of the share of education and health expenditure on the Human Development Index (HDI) in South Kalimantan and East Kalimantan provinces. The panel data regression analysis is employed using the IPM data from 2013 to 2020 and government expenditure shares in the education and health sectors across 23 districts/cities in the two provinces. The analysis reveals that the share of education and health expenditure significantly affects the HDI, while per capita income does not have a direct impact on the HDI. In conclusion, it is recommended to increase budget allocations for education and reassess the utilization of health expenditure to ensure a positive impact on the HDI. Other suggestions include considering other factors influencing the HDI, conducting further studies, and involving communities in the development process.